2005
DOI: 10.1128/jb.187.11.3869-3872.2005
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Lyase (AlgL) Activity Is Required for Alginate Biosynthesis in Pseudomonas aeruginosa

Abstract: To determine whether AlgL's lyase activity is required for alginate production in Pseudomonas aeruginosa, an algL⌬::Gm r mutant (FRD-MA7) was created. algL complementation of FRD-MA7 restored alginate production, but algL constructs containing mutations inactivating lyase activity did not, demonstrating that the enzymatic activity of AlgL is required for alginate production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 27 publications
1
50
0
1
Order By: Relevance
“…The gene encoding the P. aeruginosa periplasmic alginate lyase, algL, is located within the alginate biosynthesis cluster (12,57). Interestingly, alginate production and alginate lyase expression have been reported to be coregulated by the positive transcriptional regulator AlgB (57), and alginate lyase also plays a role in alginate biosynthesis in P. aeruginosa (1). A recent report also suggested the possible bifunctional roles of AlgL in a multiprotein secretion complex and in degrading free alginate polymers in the periplasm (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene encoding the P. aeruginosa periplasmic alginate lyase, algL, is located within the alginate biosynthesis cluster (12,57). Interestingly, alginate production and alginate lyase expression have been reported to be coregulated by the positive transcriptional regulator AlgB (57), and alginate lyase also plays a role in alginate biosynthesis in P. aeruginosa (1). A recent report also suggested the possible bifunctional roles of AlgL in a multiprotein secretion complex and in degrading free alginate polymers in the periplasm (31).…”
Section: Discussionmentioning
confidence: 99%
“…Polysaccharide lyases reported to date are (or have been predicted to be) extracellular or periplasmic (1,4,17,35,50,65). The TIGR-CMR database indicated the presence of a putative 31-amino-acid-long signal peptide in RbmB, but SignalP 3.0 (for signal peptide cleavage site prediction) did not have a strong prediction for a cleavage site (probability of cleavage between S31 and E32 is 0.319 by the SignalP-NN method and 0.023 by the SignalP-HMM method).…”
Section: Resultsmentioning
confidence: 99%
“…The periplasmic C terminus of Alg44 shares homology with the membrane fusion proteins involved in the bridging of the periplasm in multidrug efflux pumps (11,43). The periplasmic alginate lyase, AlgL, appears to be required for the translocation of intact alginate across the periplasm (1,26). AlgE is an outer membrane, anion-selective channel protein through which alginate is presumably secreted (30).…”
mentioning
confidence: 99%
“…AlgX shows little homology to any known protein, and its role is unclear (14). Knockout mutants of AlgK, AlgG, and AlgX have nonmucoid phenotypes, although they produce short alginate fragments, due to the activity of the alginate lyase (AlgL), which degrades the nascent alginate (1,14,(19)(20)(21)36). AlgF, AlgI, and AlgJ are involved in acetylation of alginate, but they are not ultimately required for its production (12).…”
mentioning
confidence: 99%
“…For the latter, AlgL could be involved in the modification of oligomers and therefore in the process to export the polymer to the cell surface. Although it has been reported that mutants defective in AlgL appeared nonmucoid and produce only small amounts of alginate (48, 67), AlgL is essentially required for alginate biosyn- thesis (2). It has also been reported that Ca 2ϩ and Mn 2ϩ can selectively activate or inhibit alginate lyase and epimerization activity in algae (35).…”
Section: Resultsmentioning
confidence: 99%